2013
DOI: 10.1161/atvbaha.113.301507
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis as a Response to High Interleukin-6 Levels in cGMP-Dependent Protein Kinase I Mutant Mice

Abstract: ; cGKI L2/L2 mice and cGKI-deficient bone marrow-chimeras. Accordingly, antibody-mediated blockade of interleukin-6 normalized platelet counts in cGKI-SM mice. Conclusions-Abnormal cGMP/cGKI signaling in nonhematopoietic cells affects thrombopoiesis via elevated interleukin-6production and results in thrombocytosis in vivo. Dysfunction of cGMP/cGKI signaling in nonhematopoietic cells contributes to a high platelet count, which is potentially associated with thrombosis. Zhang et al Thrombocytosis in cGKI-Defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In vitro, IL-6 seems to act as a megakaryocyte maturation factor and infusion of IL-6 has been shown to induce modest thrombocytosis [37], [38]. Recently, in vivo experimental studies confirmed the regulatory role of IL-6 in thrombopoiesis [39], [40]. However, in the present study, including stable, high-risk CAD patients, we found no associations between IL-6 and any platelet turnover parameters, although, IL-6 and thrombopoietin were weakly associated.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, IL-6 seems to act as a megakaryocyte maturation factor and infusion of IL-6 has been shown to induce modest thrombocytosis [37], [38]. Recently, in vivo experimental studies confirmed the regulatory role of IL-6 in thrombopoiesis [39], [40]. However, in the present study, including stable, high-risk CAD patients, we found no associations between IL-6 and any platelet turnover parameters, although, IL-6 and thrombopoietin were weakly associated.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Immunocytochemistry of bone marrow indicated that macrophages but not erythroblasts express cGKI. 1 In contrast, it was found that erythroblasts and erythrocytes purified by immunomagnetic selection using labeled anti-Ter119 MicroBeads followed by magnetic cell sorting are cGKI positive.…”
mentioning
confidence: 99%
“…Furthermore, hypoadiponectinemia has been associated with elevated levels of inflammatory markers such as C-reactive protein and IL-6 [35,36]. Elevated plasma IL-6 levels that might stem from dysfunctional cGMP/cGKI in fat cells and/or hepatic stellate cells were reported by several studies in the aRM mouse modeI [12,20,22]. This is interesting, because IL-6 may act as a negative regulator of fat cell-derived hormones such as adiponectin and vice versa IL-6 expression can be negatively regulated by adiponectin [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, we want to point out that the presented study shows preliminary data with regard to the mouse models used, because either conventional cGKI À/À or aRM mice were studied. These mice have multiple defects that are not related to the fat cell mass [21,22,30,31,[39][40][41][42]. Therefore, we cannot delineate whether or not the deletion of cGKI in fat cells was the essential cause of the reported disturbance in some fat cell parameters in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation